VOCABULARY INSTRUCTION IN READING COMPREHENSION CLASSES - DAOUDI Mourad (biblio centrale, université laghouat, 2012)
This present study is conducted to point out the role of vocabulary in improving the reading comprehension level of Master students of chemistry at the University of Laghouat. Our work is an attempt to diagnose the problematic areas that led to the reading comprehension difficulties. Consequently, we have tried to identify the causes behind their appearance in the first place, where we have actually found that these problems are due to the students’ lack of vocabulary in both General English and English for Science and Technology that is why they have the poor level in English. In fact, we thought that vocabulary knowledge represents one critical cause of comprehension problems for science learners who study in a foreign language. In the light of this, we have hypothesized that if the students of chemistry have good vocabulary knowledge; they will comprehend better when they read chemistry texts in English. To test out this hypothesis, we conducted a research in which we used two research tools, a questionnaire and a structured interview. Such a problematic requires a research design, fundamentally, based on three chapters. Chapter one presents an overview of some issues concerning EST, reading, and vocabulary. It also provide the reader with a broad description of the target situation under investigation. Chapter two is rather reserved to the methodological approach being adopted in this study. Its main focus is on the description of research design and procedure used for both processes, namely data collection and data analysis, and with the analysis and interpretation of the main findings. In the last chapter, the researcher attempts at providing new perspectives for ESP teaching in hope to promote the ESP teaching methodology for an EFL background, and thus, open the doors for further research in this particular scope of interests.
THE CASE OF M1 STUDENTS OF CHEMISTRY